Increases in global transportation-induced air pollution mortality and radiative forcing during 1990–2019 - Han, Han (Frontiers in Environmental Science, 2025)
Transportation emissions are a key source of surface fine particulate matter (PM2.5) and ozone air pollution. However, the impacts of transportation emissions on global PM2.5 and ozone over a long-term have not been documented until now. Here, we show that transportation-induced PM2.5 and ozone concentrations have increased worldwide during 1990–2019, with global means of 18% and 19% respectively. Spatially, the increases are higher over China and South Asia. We further show that global transportation-induced PM2.5 and ozone mortality has increased by 105% (315 thousand) during 1990–2019. Land transportation and air pollutant concentration are the dominant drivers of mortality increases from perspectives of transportation means and mortality influencing factors, respectively. Radiative forcing of transportation-induced PM2.5 and ozone has increased over developed countries, while decreased over developing countries during 1990–2019, with a slight global mean increase of 0.7%. Radiative forcing of transportation-induced ozone has increased across the globe, with mean changes of 23%. Increased transportation-induced PM2.5 and ozone can be effectively mitigated by emission reductions of the shared socio-economic pathways. Overall, our assessment suggests an increasing role of transportation emissions in global PM2.5 and ozone air pollution formation during 1990–2019, and highlights the necessity of abatement of transportation air pollutant emissions.